DNA typing of the gastric mucosa of patients with chronic duodenal ulcer - A. Kharchenko; A. Yelinska (Kazimierz Wielki University, 2021)
The work involved a molecular biological technique (ISSR-PCR) using ISSR-primer S-2, with structure (AGC) 6G. Changes in the gastric mucosa in chronic duodenal ulcer disease against the background of severe chronic atrophic gastritis have been analyzed. Noteworthy is the fact that there is a strong correlation between the degree of dysplasia of the epithelium of the gastric mucosa and the mitotic index, the Pearson's correlation coefficient rxy was 0.853, respectively. A strong and very strong correlation relationship between the indicators of the degree of dysplasia of the epithelium of the gastric mucosa by phenotypic characteristics and indicators of DNA typing of samples of the gastric mucosa, the Pearson's correlation coefficient rxy was 0.863, respectively. DNA profiles of the gastric mucosa of patients with duodenal ulcer according to the results of typing by the ISSR-PCR method ranging from 520 to 620 bp. had the character of microsatellite expansions and differed from the profile of the norm, which is evidence of precancerous changes.